2016
DOI: 10.1007/s11103-016-0511-6
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis reveals insights into dynamic homeostasis regulation of somatic embryogenesis in upland cotton (G. hirsutum L.)

Abstract: Plant regeneration via somatic embryogenesis (SE) is the key step for genetic improvement of cotton (Gossypium hirsutum L.) through genetic engineering mediated by Agrobacteria, but the molecular mechanisms underlying SE in cotton is still unclear. Here, RNA-Sequencing was used to analyze the genes expressed during SE and their expression dynamics using RNAs isolated from non-embryogenic callus (NEC), embryogenic callus (EC) and somatic embryos (SEs). A total of 101, 670 unigenes were de novo assembled. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 53 publications
(71 reference statements)
5
35
0
Order By: Relevance
“…Our callus differentiation rate statistics for exogenously applied auxin and cytokinin were consistent with previous studies, i.e., the induction of EC and SEs, and the concentration of 2, 4-D in the medium was replaced by a combination of IBA and KT [24,37]. In this experiment, the role of auxin and cytokinin was not achieved alone, but by interacting with other pathways and components involved in the differentiation and development of SEs, such as their upstream TF regulators and hormone signaling pathways [38]. Wang et al [39] found that, in cotton tissue cultures, the effect of IBA is stronger than that of the other auxins or auxin analogues.…”
Section: Iba Embryogenic Inductive Effect and Dose Effect During Diffsupporting
confidence: 86%
“…Our callus differentiation rate statistics for exogenously applied auxin and cytokinin were consistent with previous studies, i.e., the induction of EC and SEs, and the concentration of 2, 4-D in the medium was replaced by a combination of IBA and KT [24,37]. In this experiment, the role of auxin and cytokinin was not achieved alone, but by interacting with other pathways and components involved in the differentiation and development of SEs, such as their upstream TF regulators and hormone signaling pathways [38]. Wang et al [39] found that, in cotton tissue cultures, the effect of IBA is stronger than that of the other auxins or auxin analogues.…”
Section: Iba Embryogenic Inductive Effect and Dose Effect During Diffsupporting
confidence: 86%
“…It seems that not the initial level of IAA in explant tissue but rather a dynamic increase of the endogenous auxin content in response to the SE-induction factors might provide an indispensable signal for the embryogenic transition. Relevantly, a significant increase in the IAA content was reported to accompany early SE induction in different plants including carrot [48], sunflower [49], robusta coffee [50][51][52], alfalfa [53], pineapple guava [54], Arabidopsis [36], cotton [55] and Norway spruce [56]. Besides in vitro culture conditions, transgenic plants of Arabidopsis that produced somatic embryos in planta as a result of the overexpression of the LEAFY COTYLEDON2 (LEC2) gene were also found to accumulate IAA [57].…”
Section: Biosynthesis and Accumulation Of Auxin During Sementioning
confidence: 99%
“…More recently, RNA deep-sequencing technology has provided a platform for analysis of differences in gene expression 17 . There are reports demonstrating that hormonal signaling pathways such as auxin and cytokinin 16 , as well as stress-responsive pathways are critical during cotton SE development 18 . However, the initial SE molecular mechanisms have not been thoroughly studied and are still unclear in different dedifferentiated cotton cultivars.…”
Section: Introductionmentioning
confidence: 99%